2009
DOI: 10.1002/hlca.200800412
|View full text |Cite
|
Sign up to set email alerts
|

1,3‐Dipolar Cycloadditions of a 2‐Oxoethanenitrile Oxide Derived from (2R)‐Bornane‐10,2‐sultam to Electronically Modified 4,4′‐Disubstituted Stilbenes

Abstract: Thanks to its type-II dipole nature, we were able to demonstrate the higher reactivity of the SO 2 / C¼O syn-conformer for the uncatalyzed 1,3-dipolar cycloaddition of the 2-oxoethanenitrile oxide 2 derived from bornane-10,2-sultam to the symmetric 4,4'-disubstituted trans-stilbenes 3a -3i. The C(a)-si dipolarophile p y approach along the C¼O bond precludes the use of the steric rules formerly expressed for this pseudo-C 2 -symmetric auxiliary. The observed diastereoselectivity is related to the electronic nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…They rationalized their results on the basis of Oppolzers initial model [9a] but did not discuss the poorer diastereoselectivities observed for sterically more demanding, hence less reactive, Grignard reagents, and, moreover, did not find any electronic correlation. Since we recently demonstrated that the unchelated minor SO 2 /C¼O syn-conformer may, in some instances, be more reactive than its thermodynamically more stable anti-conformer [21] 6 ), the conformational rigidity of the N-alkenoyl side chain is primordial to the N-lp stereoelectronic control, in opposition to the C 2 -symmetrical steric influence, exerted by either the S¼O(2) or C(3) substituents, on the C(a) atom [2], hence, apparently to a much lesser extent, on the C(b) atom. We thus decided to reinvestigate, in more detail, the 1,4addition of the simple ethyl Grignard reagent to p-substituted cinnamoyl derivatives of type 2 7 ), at a conformationally rigidifying and constant low temperature, since such a 2a afforded 3a with 80% d.e.…”
mentioning
confidence: 99%
“…They rationalized their results on the basis of Oppolzers initial model [9a] but did not discuss the poorer diastereoselectivities observed for sterically more demanding, hence less reactive, Grignard reagents, and, moreover, did not find any electronic correlation. Since we recently demonstrated that the unchelated minor SO 2 /C¼O syn-conformer may, in some instances, be more reactive than its thermodynamically more stable anti-conformer [21] 6 ), the conformational rigidity of the N-alkenoyl side chain is primordial to the N-lp stereoelectronic control, in opposition to the C 2 -symmetrical steric influence, exerted by either the S¼O(2) or C(3) substituents, on the C(a) atom [2], hence, apparently to a much lesser extent, on the C(b) atom. We thus decided to reinvestigate, in more detail, the 1,4addition of the simple ethyl Grignard reagent to p-substituted cinnamoyl derivatives of type 2 7 ), at a conformationally rigidifying and constant low temperature, since such a 2a afforded 3a with 80% d.e.…”
mentioning
confidence: 99%
“…The initial analytical method was based on the integration of the Me(8) singlet in the 1 H‐NMR analysis of the crude reaction products, as earlier reported in a similar case . Although the sensitivity and precision (±2%), hence the experimental error, of the high‐field NMR method is not fundamentally modified, we now opted for a simple and direct 19 F‐NMR analysis, as earlier reported for this kind of substrates . Indeed, with CFCl 3 as reference, compound p ‐F‐ 2a exhibits two distinct diastereotopic signals at −117.39 (major) and −117.50 ppm (minor), while the p ‐CF 3 O‐ 2b and p ‐CF 3 ‐ 2c analogs exhibit displacements at −58.18/−58.23 and −62.68/−62.73 ppm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We earlier demonstrated that the nonchelated minor SO 2 /C=O syn ‐conformer may, in some instances, be more reactive than its thermodynamically more stable anti ‐conformer , thus following the Acree–Curtin–Hammett principle . Furthermore, the sense of induction may strongly depend on the chelating properties of the reagent and additives, as well as on the conformationally rigidifying low temperature of the reaction…”
Section: Discussionmentioning
confidence: 99%
“…1,3-DP cycloaddition between 2-oxoethanenitrile oxide derived from (2 r )-bornane-10,2-sultam and electronically modified 4,4′-disubstituted stilbenes was analyzed by Romanski, Chapuis, and Jurczak in terms of regioselectivity and mechanism— Scheme 189 [ 200 ].…”
Section: Syntheses Of Substituted 2-isoxazolines Via 13-dp Cycloaddit...mentioning
confidence: 99%